Новый взгляд на жёсткость дорожной конструкции при описании деформаций - Ходяков, В. А. (БНТУ, 2024)
This paper analyzes the problems of road surface deformation when a car passes through. It is proposed to expand the concept of road structure and use the concept of “rigidity of road structure” when describing its deformation.